Epidemiological and Clinical Characteristics of 5,569 Pediatric Burns in Central China From 2013 to 2019 - Han, Dawei; Wei, Ying; Li, Yancang; Zha, Xinjian; Li, Rui; Xia, Chengde; Li, Yun; Yang, Huanna; Xie, Jiangfan; Tian, Shemin (Frontiers in Public Health, 2022)
Background Pediatric burns of all the ages are prevalent worldwide, posing a severe health risk to children. This study aims to examine pediatric burns' clinical characteristics and epidemiology in central China. Methods The pediatric patients of the Burn Research Center, Department of the First People's Hospital of Zhengzhou City from 2013 to 2019 were retrospectively studied and the relevant data were collected from the hospitalized medical records [e.g., demographic, etiology, length of stay (LOS), age, gender, burn area and depth, number of surgeries, cost, and outcome]. Results A total of 5,569 pediatric burn patients were included, accounting for 43.9% of the total burn population. Electric burns represented a relatively small proportion (1.17%) but were more likely to lead to disabilities or death than scalds (90.63%) and flames (5.12%). The median age was 2 years [interquartile range (IQR): 1–4] and the boys/girls ratio ranged from 1.3:1 to 1.6:1. The most commonly burnt anatomic sites were the limbs (38.3%), with a median %TBSA (total body surface area) of 6 (IQR: 4–10). The complications of shock and pneumonia accounted for 7.6 and 19.2%, respectively. The peak months of pediatric burns included January, May, and August and the rural/urban ratio reached 1.61:1. The percentage of burn wounds treated surgically increased considerably from 2013 to 2019 (3.8 vs. 37.8%). The median hospital LOS was 15 days (IQR: 8–28 days), with the three high-risk factors (e.g., more surgeries, more %TBSA, full-thickness skin burns). The median cost of hospitalization was 1,511 USD (IQR: 848–2,648 USD) and the main risk factors consisted of full-thickness burns, more %TBSA, longer LOS, and more surgical procedures. Among all the patients, LA50 was 78.63% (95% CI = 75.12–83.45) and the overall mortality reached 0.1% since seven deaths were recorded. Conclusion Scalds, flames, contact, and chemicals are the main causes of burns among children aged 1–5 years in central China. Accordingly, various prevention strategies should be employed depending upon the cause of the burn.